Aboveground tree biomass and carbon stock of logged-over forest in Sungai Asap, Belaga - Melissa Melody, Leduning (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Global warming and climate change are intermittent issues, referring to increment in average global temperatures. These are chiefly caused by increases in greenhouse gas (GHG) viz. carbon dioxide. Malaysian Palm Oil Board (MPOB) had set up a research station to be developed as a model plantation located in Belaga to address the issue on sustainability, biodiversity and enhanced green house gas emissions (GHG). Bence, a scientific study to determine the aboveground biomass and carbon stock of the logged-over forest in Sungai Asap, Belaga was conductej The methods involved in determining the aboveground biomass and carbon stock was firstly, (i) collection of data at Sungai Asap Belaga, followed by (ii) analysis of data which involves the estimation of aboveground biomass through allometry equation. Finally, the carbon stock was estimated through conversion of the aboveground biomass value. A total of 187 tree species (46 families) were identified within the 22 quadrates of20 m x 20 m. The estimated above ground biomass of the area was 175.30 M g ha·1 where the species with the highest amount of aboveground biomass was Shorea parvifolia (Dipterocarpaceae) with 15.88 M g ha-I; followed by Macaranga triloba (Euphorbiaceae) with 14.32 M g ha-I, and Dipterocarplls aClltangllllls at 12.20 M g ha-I. The estimation of carbon stock contained in the MPOB Research Station was 82.39 M g ha-I of carbon stocks. In tropical forests, biomass and carbon content are generally high which reflects their influence on the global carbon cycle. Therefore, the aboveground biomass and carbon stock value of the logged-over forest in Sungai Asap, Belaga have large potential for the reduction ofGHG through proper conservation and sustainable management.